2017
DOI: 10.21037/cdt.2017.01.16
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of Cornell and Sokolow-Lyon electrocardiographic criteria for left ventricular hypertrophy in a military male population in Taiwan: the Cardiorespiratory fitness and HospItalization Events in armed Forces study

Abstract: Background: The Cornell and Sokolow-Lyon electrocardiography (ECG) criteria have been widely used for diagnosing left ventricular hypertrophy (LVH) in patients with hypertension. However, the correlations of these ECG criteria with LVH were rarely compared in military members who received rigorous training, particularly of the Asian male population. Conclusions: The Cornell ECG criteria for the echocardiographic LVH had better performance than the Sokolow-Lyon criteria in a young military male cohort in Taiwan. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 26 publications
(32 reference statements)
1
24
1
1
Order By: Relevance
“…10) It is reported that the diagnostic criteria for LVH can differ between races. [14][15][16][17] The aim of the present study, therefore, was to test whether this new diagnostic criterion for LVH improved sensitivity in the Japanese general population.…”
mentioning
confidence: 99%
“…10) It is reported that the diagnostic criteria for LVH can differ between races. [14][15][16][17] The aim of the present study, therefore, was to test whether this new diagnostic criterion for LVH improved sensitivity in the Japanese general population.…”
mentioning
confidence: 99%
“… 21 In 539 young army men in Taiwan, Su et al found that the Cornell voltage and product criteria had better performance for the echocardiographic LVH than the Sokolow–Lyon criteria, with a sensitivity of 22.2%, 27.8%, and 8.3%, respectively. 22 However, in 332 Korean patients seen in a cardiology department, Park et al demonstrated that the Cornell product criterion was superior to the Sokolow–Lyon voltage criterion in women, but the opposite was true in men. 23 …”
Section: Discussionmentioning
confidence: 99%
“…У хворих на ДАК дітей не було зафіксовано клінічних та допплерехокардіографічних ознак серцевої недостатності .Кардіографічний Індекс Соколо-А. В. Каменщик © Сумський державний університет, 2018 ва-Лайона (ІСЛ) розраховувався як сума біоелектричних потенціалів зубців S1 й максимального зубця R5 чи R6 (mV) у грудних відведеннях [7,8], Корнельський вольтаж ний індекс (КВІ) розраховувався як сума біоелектричних потенціалів зубця R у відведенні aVL (R VL) та зубця S у відведенні V3 [ 9,10]. Тривалість електричної систоли шлуночків (ТС) розраховувалась як довжина інтервалу Q-T у секундах [11].…”
Section: вступunclassified